Romosozumab: A first-in-class sclerostin inhibitor for osteoporosis. (3rd September 2020) - Prather, Caitlin; Adams, Erin; Zentgraf, Whitney
Abstract: Purpose: The purpose of this article is to review the pharmacology, efficacy, and safety of the sclerostin inhibitor romosozumab for the treatment of osteoporosis, including data from clinical trials of the drug. Summary: A review of the literature was performed by searching PubMed and MEDLINE for all relevant articles published between January 2014 and February 2020 using the keywords romosozumab, romosozumab-aqqg, osteoporosis, and fracture . All relevant English-language articles evaluating the pharmacology, efficacy, or safety of romosozumab for the treatment of osteoporosis in humans were included; poster presentations were excluded. Romosozumab has been approved by the Food and Drug Administration and is considered both safe and effective for the treatment of osteoporosis in high-risk postmenopausal females. Phase 2 and phase 3 clinical trials have shown a statistically significant decrease in new vertebral fractures and an increase in bone mineral density with romosozumab use, as compared with both placebo use and use of alternative osteoporosis therapies. The primary safety concern is a potential risk of cardiovascular events; additionally, hypocalcemia must be corrected prior to initiation. Romosozumab is the first anabolic medication that both increases bone formation and decreases bone resorption. Data suggest that romosozumab is more effective than oral bisphosphonates in preventing osteoporotic fractures, though cost and safety concerns must be considered. Conclusion: Romosozumab is a novel, 12-month treatment option for postmenopausal women at high risk for osteoporotic fracture that both increases bone formation and decreases bone resorption.